VD_FINDINFO Décision / 2014 / 872 vom 10. Oktober 2014 - VD Tribunal cantonal (2014)
DÉTENTION PROVISOIRE, SOUPÇON, RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH), 222 CPP (CH)